THE EFFECT OF PERCEIVED CONVENIENCE, PERCEIVED BENEFITS, AND TRUST ON INTENTION TO USE MOBILE BANKING - Apriani, Riska Gabrie; Respati, Dwi Kismayanti; Handarini, Dwi (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
This study aims to determine the effect of perceived ease of use on the intention to use mobile banking, perceived usefulness on the intention to use mobile banking, and trust on the intention to use mobile banking, as well as the combined effect of perceived ease of use, perceived usefulness, and trust on the intention to use mobile banking among students of the Accounting Department of the State University of Jakarta, class of 2019. The population for this study comprised 179 students. Stratified Random Sampling was conducted with specific criteria, resulting in a sample of 124 students. This research is guided by the TAM (Technology Acceptance Model) Theory. The study reveals that perceived ease of use has a negative and insignificant effect on the intention to use mobile banking, thus rejecting H1. However, perceived usefulness have a positive and significant effect on the intention to use mobile banking, supporting H2. Trust also has a positive and significant effect on the intention to use mobile banking, validating H3. Furthermore, perceived ease, perceived usefulness, and trust collectively have a positive and significant effect on the intention to use mobile banking, confirming H4.